2013
DOI: 10.1037/lhb0000011
|View full text |Cite
|
Sign up to set email alerts
|

How factors present during the immediate interrogation situation produce short-sighted confession decisions.

Abstract: Suspects have a preexisting vulnerability to make short-sighted confession decisions, giving disproportionate weight to proximal, rather than distal, consequences. The findings of the current research provided evidence that this preexisting vulnerability is exacerbated by factors that are associated with the immediate interrogation situation. In Experiment 1 (N = 118), a lengthy interview exacerbated participants' tendency to temporally discount a distal consequence when deciding whether or not to admit to cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 41 publications
4
50
0
2
Order By: Relevance
“…Exhaustion encourages the detainee to believe in promises of leniency and minimisation or maximisation tactics and the false idea that the justice system will in the end recognise innocence and not take into account the false confession. Madon, Yang, Smalarz, Guyll, & Scherr (2013) have shown in a series of experimental studies how the length of the interview (even the expectation of length) results in short-sighted decisions to confess, irrespective of whether the subject is innocent. Davis and Leo (2012) have developed a model that links basic routine elements of a law-enforcement interrogations to confessions called the IBRD (Interrogation-Related…”
Section: S C I E N T I F I C a R T I C L Ementioning
confidence: 99%
“…Exhaustion encourages the detainee to believe in promises of leniency and minimisation or maximisation tactics and the false idea that the justice system will in the end recognise innocence and not take into account the false confession. Madon, Yang, Smalarz, Guyll, & Scherr (2013) have shown in a series of experimental studies how the length of the interview (even the expectation of length) results in short-sighted decisions to confess, irrespective of whether the subject is innocent. Davis and Leo (2012) have developed a model that links basic routine elements of a law-enforcement interrogations to confessions called the IBRD (Interrogation-Related…”
Section: S C I E N T I F I C a R T I C L Ementioning
confidence: 99%
“…As discussed, colleagues (2012, 2013) developed an interrogation paradigm to investigate the possibility that temporal discounting serves as a mechanism underlying the elicitation of false information in interrogation. Their findings supported this supposition: When questioned about their engagement in a variety of criminal and unethical behaviors, young adults altered their responses so as to avoid the proximal consequence even though doing so put them at increased risk of incurring a more severe distal consequence (Madon et al, 2012(Madon et al, , 2013. Adolescents, because of developmental deficits in future orientation, may be even more likely to avoid incurring undesirable proximal consequences in favor of potentially more severe distal consequences.…”
Section: Dispositional Risk Factorsmentioning
confidence: 86%
“…Specifically, previous research has reported either no suspicion (Madon et al, 2012(Madon et al, , 2013, a suspicion rate of less than 1% (Madon et al, 2013;Yang et al, 2015), or a maximum suspicion rate of approximately 3.5% (Madon et al, 2012). However, differences in suspicion rate may be due to the criteria used to exclude participants for suspicion.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
See 2 more Smart Citations